Explaining social welfare expansion in Hong Kong and South Korea the relevance of comparative policy paradigms of industrialization and labor mobilization - Tang, Kwong-Leung; Lee, Sun-Woo (2000)
The question of what explains social welfare development over the world has been haunting researchers for some time. Different theories are formulated to account for this phenomenon, though conflicting empirical findings result from these theories. In the study of comparative social welfare development, two dominant theories stand out: the industrial society perspective (convergence theory) and the labor mobilization model. They both advance their arguments in the social structural term. Their validity for other parts of the world has not been established. The article examines whether these two theories can be applied to the East Asian Newly Industrializing Countries (NICs). Hong Kong and South Korea are selected as the focus of this study. Using quantitative regression methods, hypotheses derived from these two theorethical standpoints are tested. The empirical study arrives at the following conclusions: (1) evidence for welfare convergence is rather weak, and (2) the industrial society perspective seems to be a stronger model to explain social welfare growth in these two countries than the labor mobilization model.
Keywords: Economic development -- Hong Kong; Economic development -- South Korea; Public welfare policy -- Hong Kong; Public welfare policy -- South Korea